Assessment of the effects of insecticide Basudin (Diazinon) on common carp (Cyprinus carpio) in a rice based agro-ecosystems - Mohiuddin, Md.; Phillips, Michael John; Edwards, Peter; Little, David C.; Government of Britain (Bangkok : Asian Institute of Technology, 1993)
A short term toxicity test of an organophosphate insecticide, basudin 60EC (diazinon) was carried out on Common carp (Cyprinus carpio) in laboratory condition. The LC50 at 24, 48, 96 hours exposure to diazinon were 4.42, 3.33, and 2,40 ppm respectively. The safe concentration of diazinon was calculated as 0.56 ppm from the short term toxicity test for Cyprinus carpio presumed to be harmless concentrat ion. A long term test was set up in rice field to assess the long term effects of diazinon to Common carp. Diazinon was applied at various concentrations (1.0, 2.0, 4.0, 8.0 ppm), The LC50 in field conditions is much higher than the LC50 value observed in short term toxicity test. The results clearly indicated that the lethal effects of diazinon were insignificant in rice field environment due to the effects of various environmental factors. Water quality was not affected by the insecticide spraying but temperature, suspended solids, solar radiat ions and other environmental factors was likely to influence the toxicity of diazinon. Fish yield was not significantly different between treatments but comparatively the highest yield (481 kg/ha) was in 1.0 ppm treatment associated with survival rate and growth rate. No significant differences in rice yields were observed. Based on the present study, diazinon application rate of 1.0 ppm in rice field conditions may be considered as recommended dose for rice-fish culture system.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1993
Keywords: Pesticides -- Physiological effect; Fishes -- Effect of pesticides on